2016
DOI: 10.1111/cch.12315
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of parents and children, participating in a school‐based feeding programme in disadvantaged areas in Greece: a qualitative study

Abstract: The present findings indicate that although the traditional Mediterranean diet was perceived by the majority of the adults as a health and traditional dietary pattern, parents reported several barriers related to its adoption. In particular, the most common barriers included financial difficulties, limited time for food preparation and children's resistance to consume healthy foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Policies and practices aimed at promoting healthy eating in schools should also consider the influence of socioeconomic inequalities on adolescent eating behaviors, provide nutritional information, and consider the important nurturing role that mothers play in their children's diet (Dalma et al, 2016) while reinforcing the father's role in promoting healthy eating habits among their children.…”
Section: Socioeconomic Status and Nutritionmentioning
confidence: 99%
“…Policies and practices aimed at promoting healthy eating in schools should also consider the influence of socioeconomic inequalities on adolescent eating behaviors, provide nutritional information, and consider the important nurturing role that mothers play in their children's diet (Dalma et al, 2016) while reinforcing the father's role in promoting healthy eating habits among their children.…”
Section: Socioeconomic Status and Nutritionmentioning
confidence: 99%
“…This study identified general barriers which were situated on all levels of the socio-ecological model of health behaviour: the individual level (e.g., lack of energy and motivation for PA, unhealthy family traditions for limiting SB and unhealthy dietary preferences for healthy dietary habits); interpersonal level (e.g., lack of time for PA and bad role models for dietary habits); organisational level (e.g., lack of facilities in the neighbourhood and at home for PA and having homework for limiting SB) and macro/public policy level (e.g., the current technology nation and unfavourable weather circumstances for limiting SB). Some of these general barriers (e.g., lack of energy, time and facilities for PA, unhealthy family traditions for limiting SB and healthy cooking being time-consuming for healthy dietary habits) were also reported in previous, nationally conducted studies investigating barriers experienced by socially disadvantaged families [20,21,22,23,24,25], which might imply that these barriers indeed play an important role in the lifestyle behaviours of families living in vulnerable areas. Additionally, this study shows that these barriers apply at a European level, as these barriers were reported across different European countries.…”
Section: Discussionmentioning
confidence: 87%
“…A first important step in developing an intervention for this target group is to gain insight into the barriers that they experience towards healthy lifestyle behaviours. Studies investigating barriers perceived by families living in vulnerable areas from parents’ perspective show that, for example, financial constraints [20,21], parents’ busy work schedules [20], lacking time to purchase and prepare healthy foods [20,21,22], children’s resistance in consuming healthy foods [20,21], lack of support from friends and/or family in adopting healthy dietary habits [22,23] and unhealthy food preferences of both the partner and children [22] are barriers to healthy dietary habits. Lack of time [23], feelings of exhaustion [23], lack of opportunities for participation in physical activity (PA) [24], difficulties with transportation [24], lack of facilities and space at home [25], sports activities being too expensive [24] and children disliking PA [24] are barriers to sufficient PA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of healthy eating was acknowledged by participants in the majority of studies, and participants perceived healthy eating as desirable (Backett-Milburn, Wills, Gregory, & Lawton, 2006;Baumann, Szabo, & Johnston, 2019;Boshoff, Dollman, & Magarey, 2007;Calnan, 1986;Dalma et al, 2016;Dibsdall et al, 2002;Dressler & Smith, 2013;Dye & Cason, 2005;Eikenberry & Smith, 2004;Engler-Stringer, 2010;Fielding-Singh, 2017Fielding-Singh & Wang, 2017;Herman, Malhotra, Wright, Fisher, & Whitaker, 2012 Five items answered with 'yes' Six items answered with 'yes' Seven items answered with 'yes' Eight items answered with 'yes' Nine items answered with 'yes' Ten items answered with 'yes' 1 0 2 9 18 3 Note: a: Total number of individual participants, e.g. 30 parents and 30 children in a study is considered 60 participants; five focus groups of each five participants is considered 25 participants in total; b: This checklist was designed for qualitative research; therefore, two quantitative studies were not assessed and the total number of studies in this row is 33.…”
Section: Notions Of 'Healthy' and 'Good' Eatingmentioning
confidence: 99%